Akibat Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Pencurian Yang Menyebabkan Kematian (Studi Putusan Nomor : 45/Pid.Sus-Anak.2018/PN. Lbp) - Denny Hardi Pranata Saragih; Rizkan Zulyadi; Dessy Agustina Harahap (JUNCTO: Jurnal Ilmiah Hukum, 2019)
Children according to language are the second offspring as a result of male and female relationships. In consideration of Law No. 23 of 2002 concerning the protection of children, it is said that children are the mandate and gift of God Almighty, which is inherent in their dignity and dignity as whole human beings. The research method used is the author uses a type of Empirical Law research which is a legal research method that functions to look at the law in the real sense and examine how law works in the community. Because in this study examines people in living relationships in the community, the empirical legal research methods can be said as sociological legal research. Based on the position of decision case number 45 / Pid.Sus-Anak / 2018 / PN Lbp factors that cause children to commit crime are economic factors and are invited by friends and excessive lifestyle.